PENERAPAN SANKSI PIDANA TERHADAP PELAKU PROSTITUSI ONLINE DI YOGYAKARTA - Miftah Raharjo; Lilik Mulyadi (Universitas Janabadra, 2017)
The purpose of this research is to know the factors influencing judges consideration in dropping criminal verdict against the perpetrator of online prostitution and to know and explain about judge decision, have been fair in giving sanction of prostitution crime online in Yogyakarta. The research was conducted in Yogyakarta Special Region with the location of Yogyakarta District Court, the type of research is Normative Juridical Law Research, which is Type of Research which focused to study the application of norm or rule in positive law. Normative research can be interpreted as research conducted by examining library materials or secondary data consisting of primary materials, secondary legal materials, and tertiary legal materials. 1 The materials are arranged systematically, reviewed and then drawn conclusions in relation to the problem under study. The nature of the research is an analytical descriptive research that is a study that describes the situation, the actual facts against the object and the subject studied appropriately. The data have been collected from the research, both literature research and field research, then analyzed descriptively qualitative, that is a method of data analysis by grouping and selecting data obtained from research according to quality and correctness.2 The results of this study indicate that the judge's consideration in imposing criminal sanction on the perpetrators of online crime of prostitution is that the judges have done their best to consider juridically consisting of the indictment of the public prosecutor, the defendant's statements, witness statements, evidence, and articles of criminal law and the judge also consider non juridically consisting of the background and motivation of the defendant's conduct, then the judge takes into account and considers both the report of the investigator and the legal facts revealed in the hearing and the various laws governing the ITE legislation, the trafficking of persons and pornography.